Analisis Kemampuan Literasi Numerasi Ditinjau dari Efikasi Diri pada Peserta Didik SMP - Salsabilah, Adinda Putri; Kurniasih, Meyta Dwi (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2022)
Numerical literacy ability is currently most highly discussed in education. Numerical literacy ability is the ability that forms the basis for students in solving mathematical problems and is one of the indicators for the Minimum Competency Assessment (AKM). This study analyzes numeracy literacy skills regarding self-efficacy in junior high school students. The research method used in this research is descriptive qualitative. The data was taken using a questionnaire and an essay test instrument. The subjects in the study were students who represented the category of self-efficacy, namely students with low, medium, and high abilities. The results showed that students in the high self-efficacy category met four indicators of numeracy literacy skills, namely, the problem understanding process, the problem modeling process, the process of using concepts in solving problems, and the process of interpreting and evaluating problems. Students with moderate self-efficacy fulfill three indicators of numeracy literacy skills: problem understanding, problem modeling, and the process of using concepts in solving problems. Meanwhile, students with low self-efficacy fulfill one indicator of numeracy literacy ability, namely the process of understanding the problem. Therefore, the results of this study indicate that the better the students' self-efficacy, the better their numeracy literacy skills are.